PENGUJIAN UMUR SIMPAN GETUK TINGGI PROTEIN CITARASA REMPAH: Shelf Life Testing Getuk High Protein Spice Flavor - Agnes Juniarti Chastelyna; Sedarnawati Yasni; Didah Nur Farida (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2023)
This study aims to extend the shelf life of getuk by adding mung beans, then diversify the taste of the product by adding ginger or cinnamon essential oil. In the first stage of making high protein getuk, there are three formulas, namely original getuk (GO), ginger flavored getuk (GJ), cinnamon flavored getuk (GK). The next step is to determine the shelf life of spice-flavoured high-protein getuk stored at room temperature of 25°C in a desiccator to avoid contamination and in a refrigerator at a temperature of 5°C for 7 consecutive days. Observations were made on the total number of microbes using the TPC (total plate count) method with the medium used was Plate Count Agar (PCA). Storage using a refrigerator at a temperature of 5°C and room temperature of 25°C in a desiccator on days 0, 1, and 2 the total number of bacteria that grew below 104 for all high-protein getuk formulas, but on day 3 the total number of bacteria already above the maximum value allowed by BPOM in 2019. Similar to room temperature storage, spice-flavoured high-protein getuk cannot extend shelf life but can reduce the total number of microbes in each sample.